Differential replicative fitness of the four dengue virus serotypes circulating in Colombia in human liver Huh7 cells - Hernando Gutiérrez-Barbosa; Nadia Y. Castañeda; Jaime E. Castellanos (Brazilian Journal of Infectious Diseases, 2020)
Dengue has been a significant public health problem in Colombia since the simultaneous circulation of the four dengue virus serotypes. The replicative fitness of dengue is a biological feature important for virus evolution and contributes to elucidating the behavior of virus populations and viral pathogenesis. However, it has not yet been studied in Colombian isolates. This study aimed to compare the replicative fitness of the four dengue virus serotypes and understand the association between the serotypes, their in vitro infection ability, and their replication in target cells. We used three isolates of each DENV serotype to infect Huh-7 cells at an MOI of 0.5. The percentage of infected cells was evaluated by flow cytometry, cell viability was evaluated by MTT assay, and the pathogenicity index was calculated as a ratio of both parameters. The replicative fitness was measured by the number of viral genome copies produced using quantitative PCR and the production of infectious viral progeny was measured by plaque assay. We showed that Huh-7 cells were susceptible to infection with all the different strain isolates. Nevertheless, the biological characteristics, such as infectious ability and cell viability, were strain-dependent. We also found different degrees of pathogenicity between strains of the four serotypes, representative of the heterogeneity displayed in the circulating population. When we analyzed the replicative fitness using the mean values obtained from RT-qPCR and plaque assay for the different strains, we found serotype-dependent behavior. The highest mean values of replicative fitness were obtained for DENV-1 (log 4.9 PFU/ml) and DENV-4 (log 5.28 PFU/ml), followed by DENV-2 (log 3.9 PFU/ml) and DENV-3 (log 4.31 PFU/ml). The internal heterogeneity of the replicative fitness within each serotype could explain the simultaneous circulation of the four DENV serotypes in Colombia.